Sistem Deteksi Tingkat Kematangan Pada Tapai Singkong Berdasarkan Data Sensor pH dan Kadar Alkohol Berbasis Embedded System - Nurul Ikhsan; Dahnial Syauqy; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tapai cassava is one of the traditional processed food products in Indonesia. Tapai cassava changes the fermentation process that turns cassava into tapai with the help of tapai yeast, We can say about people who would like cassava which has sweet taste, soft texture and a little alcohol content. Yeast will then produce tapai which has high water content, high acidity, very high texture and becomes acidic which contains a very sharp and alcoholic aroma. By knowing to the level or alcohol in cassava tapai, we can find out the future level of cassava tapai, whether tapai is not yet ripe, ripe, or too ripe for consumption. From this explanation, the researchers made a Maturity Level System in Cassava Based on Ph Sensor and the Embedded Alcohol Based Alcohol Level Data that can help the public or connoisseurs to achieve what has reached, which has been produced, which has been produced or that has been produced. In this system several components are used, namely the Arduino Uno microcontroller for data processing and for classification using the k-Nearest Neighbor method, the SEN0161 pH meter sensor and the MQ-3 sensor used to measure alcohol content and levels of cassava. In this system after testing the value of K, k9 is obtained as the best K with a percentage of 100% and for testing the accuracy of the test is 86.66% and the average rat error in the system is 13.34%, the tests produced at produce from the nearest k-neighbor classification.Keywords: cassava tapai, mq3 sensor, ph sensor, k-nearest neighbor